2016
DOI: 10.1111/auar.12087
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Notes to the Financial Statements and the Adoption of IFRS

Abstract: Summary at a glance This study examines the association between the readability of financial disclosures and IFRS adoption in Australia. Results show that the Notes (the Notes) to the Financial Statements are significantly lengthier, yet are more readable in the post‐IFRS period. Further, the disclosures in the Summary of Significant Accounting Policies, Financial Instruments and Intangible Assets drive the increased length of the Notes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 42 publications
4
24
1
Order By: Relevance
“…The results showed that the adoption of homogenous accounting standards does not necessarily result in similar implications, as cultural, social, and institutional factors influence this relationship. While in the Australian context Cheung and Lau (2016) observed an improvement in the readability level of the reports, Jang and Rho (2016) demonstrated that, compared with the Korean normative standard, IFRS adoption did not result in greater readability; however, it did moderate the relationship between factors such as firm age and ownership structure, reinforcing an improvement in readability level.…”
Section: Does Disclosing More Mean Users Are Morementioning
confidence: 93%
See 2 more Smart Citations
“…The results showed that the adoption of homogenous accounting standards does not necessarily result in similar implications, as cultural, social, and institutional factors influence this relationship. While in the Australian context Cheung and Lau (2016) observed an improvement in the readability level of the reports, Jang and Rho (2016) demonstrated that, compared with the Korean normative standard, IFRS adoption did not result in greater readability; however, it did moderate the relationship between factors such as firm age and ownership structure, reinforcing an improvement in readability level.…”
Section: Does Disclosing More Mean Users Are Morementioning
confidence: 93%
“…The Readability Problem The problem of readability has already been studied in the field of accounting and auditing. Recent studies have consolidated the evidence on its determinants (Seifzadeh et al, 2020), as well as observing its implications in relation to audit quality (Salehi et al, 2020), earnings quality (Luo et al, 2018), cost of capital (Bonsall & Miller, 2017), and the adoption of the International Financial Reporting Standards (IFRS) (Cheung & Lau, 2016).…”
Section: Does Disclosing More Mean Users Are Morementioning
confidence: 99%
See 1 more Smart Citation
“…Overall length refers to the total number of words analyzed in a document and may be used as an impression management tactic (Cheung & Lau, ; Conway, O'Keefe, & Hrasky, ). One argument is that longer letters are used as a device to obscure negative news (Conway et al, ).…”
Section: Hypothesesmentioning
confidence: 99%
“…In other cases, companies report according to the Czech legislation. For example, the research conducted by Cheung and Lau (2016) has shown that financial reports are significantly lengthier, yet are more readable in the post-IFRS period (after adopting IFRS reporting in the company). Further, the length of disclosures in Summary of Significant Accounting Policies, Financial Instruments and Intangible Assets are significantly longer after the adoption of IFRS.…”
Section: Accounting Regulation On Intangibles In the Czech Republicmentioning
confidence: 99%